Systems simulation by graphs - Волков, A. A. (Proceedings of National Aviation University (archive), 1998)
Substained on the basis of general theoretical multiple model is the concept of system simulation by graphs, determined are conceptions of simulating and generalized simulating graphs as the basis for data base construction and intellectual systems of processing information and control